Psychotherapy-Based Self-Talk by Imam Junaid Al-Baghdadi (Musyawarotun Nafsi) as an Effort to Overcome the Quarter-Life Crisis: Self-Talk Berbasis Psikoterapi Karya Imam Junaid Al-Baghdadi (Musyawarotun Nafsi) Sebagai Upaya Mengatasi Quarter Life Crisis - M. Arifurrahman; Fitri Kamilia Azzahra; Fajri Fauzan Azhari (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The transition to adulthood (emerging adulthood) is a period that is prone to quarter life crisis. If allowed to drag on and not adaptively regulated, it is possible that the crisis period will have a negative impact on the physical, psychological, and spiritual state of the individual. Therefore, a way to deal with this is needed, especially from the perspective of Islamic (sufistic) psychology. The purpose of this study is to examine and analyze the understanding of Imam Junaid al-Baghdadi's self-talk theory (Musyawarotun Nafsi) in an effort to overcome the quarter life crisis. This research uses a qualitative approach, with data collection techniques in the form of literature studies. The data presentation method used is descriptive- analytic. The result of this research is that according to Imam Junaid al-Baghdadi, humans have three elements of the soul, namely lust, qalb, and spirit and aql. Lust is the source of mental disorders in humans. Therefore, the three elements need to be harmonized in order to be balanced. Musyawarotun Nafsi (soul-talk) or self-talk by Imam Junaid al-Baghdadi is a way that can be done to balance the three elements. In conclusion, Imam Junaid al- Baghdadi's self-talk can help individuals to recognize their problems, recognize themselves, and recognize their God. It has the concept of focusing on improving current and future circumstances, so conceptually Imam Junaid al-Baghdadi's self-talk can be applied to deal with quarter life crisis.